2020
DOI: 10.3389/fphys.2020.612928
|View full text |Cite
|
Sign up to set email alerts
|

3D Compressed Convolutional Neural Network Differentiates Neuromyelitis Optical Spectrum Disorders From Multiple Sclerosis Using Automated White Matter Hyperintensities Segmentations

Abstract: BackgroundMagnetic resonance imaging (MRI) has a wide range of applications in medical imaging. Recently, studies based on deep learning algorithms have demonstrated powerful processing capabilities for medical imaging data. Previous studies have mostly focused on common diseases that usually have large scales of datasets and centralized the lesions in the brain. In this paper, we used deep learning models to process MRI images to differentiate the rare neuromyelitis optical spectrum disorder (NMOSD) from mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…In the previous study, we found that AccuBrain ® could accurately segment and measure hippocampus volume like FreeSurfer, a well-used tool for brain structure measurement worldwide (Abrigo et al, 2019 ). We also proved that AccuBrain ® had good accuracy and reproducibility in segmenting and measuring WMHs, especially in 3D T2-weighted fluid-attenuated inversion recovery (T2-FLAIR) MRI (Guo et al, 2019 ; Wang et al, 2020b ). Different from previous studies, this cross-sectional study not only explored the relationship between WMHs and quantitative medial temporal lobe atrophy (QMTA) but also analyzed the correlation between WMHs and atrophy of occipital, temporal, frontal, parietal, and insular lobe.…”
Section: Introductionmentioning
confidence: 63%
“…In the previous study, we found that AccuBrain ® could accurately segment and measure hippocampus volume like FreeSurfer, a well-used tool for brain structure measurement worldwide (Abrigo et al, 2019 ). We also proved that AccuBrain ® had good accuracy and reproducibility in segmenting and measuring WMHs, especially in 3D T2-weighted fluid-attenuated inversion recovery (T2-FLAIR) MRI (Guo et al, 2019 ; Wang et al, 2020b ). Different from previous studies, this cross-sectional study not only explored the relationship between WMHs and quantitative medial temporal lobe atrophy (QMTA) but also analyzed the correlation between WMHs and atrophy of occipital, temporal, frontal, parietal, and insular lobe.…”
Section: Introductionmentioning
confidence: 63%
“…Two of them used different biomarkers and ML learning classifiers to distinguish MS from Neuromyelitis Optical Spectrum Disorders (NMOSD) ( 53 , 54 ). The first article employed a CNN for lesion segmentation of MRI images on 213 patients with MS and 125 patients with NMOSD.…”
Section: Resultsmentioning
confidence: 99%
“…54 publications were grouped into 4 categories based on the application of ML Learning in MS disease.…”
mentioning
confidence: 99%
“…Due to limited available data, they primarily utilized SqueezeNet to prevent overfitting, achieving an accuracy of 0.81, sensitivity of 0.80, and specificity of 0.83 using common features to classify MS and NMOSD. Wang et al (2020) compressed 3D MS and NMOSD MRI images into multi-channel 2D images and used a 2D ResNet model for classification. By leveraging transfer learning subsequent to pre-training the model on ImageNet, they attained an accuracy of 0.75.…”
Section: Related Workmentioning
confidence: 99%